Det usikre sangerlivet En livshistoriestudie på langs og på tvers i klassiske sangeres sosiale praksis - Vesterlid Strøm, Regine (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
Uncertainty at many levels in classical singers' career trajectories and professional practice is a fulcrum in this book. Produced through life history interviews with 14 professional Scandinavian singers, born between 1945 and 1978, the study follows the participants' experiences of possibilities and limitations of action through their life course. It obtains some of the prerequisites that underpin the practical knowledge of the singer considering the cultural traditions of classical singing and the hierarchical field of music the singers aim for and act within. The overarching theoretical framework is founded in Pierre Bourdieu's theory of practice, but the study has an interdisciplinary approach. Here, the pluralistic life course perspective forms the basis for understanding processes and changes over time. The study shows how singers' choices and strategies, reflections, opinions and preferences, can be understood in relation to their backgrounds, and their social positions in the classical music field where music is the interconnecting element. A comprehensive feature of the research material is how uncertainties are expressed as assessments as an answer to the uncertainty that characterizes singers as well as singing education, singing performance and the singing profession. This dominant practice of assessment is interpreted as a circular phenomenon, where the assessment culture becomes a consequence of uncertainty, while increasing uncertainty.